Drugs being tested against covid-19 to slow down its spread and find effective treatment: A systematic review. - Rasheed , Arsalan; Μalaika Νοοr; Usman, Τahir; Rizwana Bilqees; Muhammad Afnan; Saira Gul; Khan, Naimat Ullah; Khattak, Saadullah; Khattak , Irfan; Shah , Assar Ali (International Journal of Endorsing Health Science Research, 2022)
Background: The SARS-COV-2's spread from continent to the continent has resulted in an increased number of mutations in the viral gene encoding proteins. As a result, mutations in target proteins provide a significant challenge in creating antiviral drugs and vaccines. The present review discussed the COVID-19 epidemiology and the effects of drugs being tested against COVID-19/SARS-COV-2. Dosage of these drugs along with associated challenges was also discussed. Methodology: Systematic review was conducted after a thorough search in the "PubMed, NIH, Elsevier, Scopus, Web of Science, Science Direct, and Google Scholar database. 45 studies on drugs associated with COVID-19 fulfilled the inclusion criteria and were selected for this review. Results: The FDA only accepted the Remdesivir drug against SARS-COV-2, as the hospitalized patients recovered very quickly by taking it. Antiviral EIDD-2801 has been found to make the SARS-COV-2 unable to infect cells by causing genetic modifications in the virus RNA. Similarly, Nitazoxanide appeared beneficial against SARS-COV-2 in a primary intervention and severe conditions (including pregnancy) without undesirable effects on the newborns. Children with mild cases can be handled solely by proper caring. Conclusion: Although Remdesivir and Dexamethasone are recommended in severe cases, clinical trials are ongoing to investigate other possible therapies like MAb and Convalescent Plasma antibodies for COVID-19. Older drugs (usually used to treat other conditions) are also under-tested by researchers to see if they are effective for COVID-19. Further tests are essential to validate whether any of the mentioned above possible therapies would be helpful for COVID-19 treatment.